Участь органів самоврядування Херсона та Миколаєва в розбудові міського господарства в другій половині ХІХ ст. - Дорошева, Антоніна Олександрівна; Dorosheva, Antonana O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Досліджено роль інститутів міського самоврядування Херсона та Миколаєва в розбудові міського госпо-дарства в 60–90-х рр. ХІХ ст., що, насамперед, полягало в знаходженні підрядчиків, відведенні міської землі для будівництва, керівництві процесом розробки необхідних проектів і координації здійснюваних робіт.The essay of presented here investigates the role of self-government institutions of Kherson and Nikolayev in the municipal economy in the 60-th-90-th of the ХІХ-th century. Their main task was selection of contractors, allotment of the city land for construction, management of the necessary projects and coordination of all activities. The main tasks the city municipalities needed solve were the road repairing and building of new ones; the inculcation of electric lighting; the forming of the municipal budget; the providing of the inhabitants with fresh water; the opening of new economic organizations; the planting of greenery. Such projects as the road building and its repairing, the appearance of central water – supply were successfully realized in the towns of Nikolayev and Kherson in the second half of the XIX century. The electric lighting was inculcated on the whole at the enterprises, factories and plants in 90-s of the XIX century. During that period of time the town incomes increased several times as many in comparison with the beginning of the XIX century.
The Role of Self-government Institutions of Kherson, Nikolayev in Alteration of City Economy (2-nd Half of the ХІХ-th Century)
Keywords: органи міського самоврядування; міське господарство; міське громадське управління; муніципальне підприємство; міська дума; міська управа; the organs of city self-government; city public management; municipal economy; municipal production